Trees : their natural history - Thomas, Peter, 1957- (Cambridge University Press, 2000)
"This book provides a comprehensive introduction to the natural history of trees, presenting information on all aspects of tree biology and ecology in an easy-to-read and concise text. Insights into the workings of these everyday plants are uncovered throughout the book, with questions such as how trees are designed, how they grow and reproduce, and why they eventually die, tackled in an illuminating way. Written for a non-technical audience, the book is none the less rigorous in its treatment and will therefore provide a valuable source of reference for beginning students as well as those with a less formal interest in this fascinating group of plants."--Jacket